Предмет: Алгебра,
автор: Аноним
Помогите пожалуйста продифференцировать
(4x-3)^5(2-x)^6
Ответы
Автор ответа:
1
((4х-3)^5 * (2-х)^6)' = ((4х-3)^5)' * (2-х)^6 + ((2-х)^6)' * (4х-3)^5 = 5*(4х-3)^4*(4х-3)'*(2-х)^6 + 6*(2-х)^5*(2-х)'*(4х-3)^5= 5*(4х-3)^4*4*(2-х)^6 + 6*(2-х)^5*(-1)*(4х-3)^5= 20*(4х-3)^4*(2-х)^6 - 6*(2-х)^5*(4х-3)^5
Похожие вопросы
Предмет: Информатика,
автор: kookie59
Предмет: Английский язык,
автор: lenavdae
Предмет: Алгебра,
автор: Аноним
Предмет: Математика,
автор: Leila111111111
Предмет: Математика,
автор: anna67038